PENERAPAN E-GOVERNMENT PADA DINAS PERTAMBANGAN DAN ENERGI PROVINSI KALIMANTAN TENGAH BERBASIS WEBSITE - Oktaviyani, Enny Dwi; Sahay, Abertun Sagit; Inso, Lius Kaharap Bion (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2014)
Currently a governmental agency has many uses a centralized system that nature, where theimportant data and information can be accessed through an online computerized system. E-Governmentis the use of information technology by the government to provide information and services with citizens,businesses, and other matters relating to the administration. With the implementation of E-Government atthe Department of Mines and Energy of the Province of Central Kalimantan is expected to assist thedelivery of accurate and reliable information becomes easier with the service provided and as the use ofGeographic Information System (GIS), the delivery reports of the company to be faster, information to thepublic the mining world as well as data management personnel.Implementation of E-Government at the Department of Mines and Energy of the Province ofCentral Kalimantan made using Waterfall method for design and analysis steps, web 2.0 technology withprogramming languages HTML, PHP, CSS, and JavaScript based Content Management of System (CMS)and have techniques for web development using Ajax and JQuery to create a website to be interactivewith picture effects, themes, etc..Kalteng DISTAMBEN this website, is one form of implementation of services such as informationand communication by using a computerized system that can facilitate services to parties / other agenciesand to the general public in the process of finding the location, determine the shape of the service areasof Distamben, sending a message and reports. Equipped with a CMS that is used to manage the content ofthe website, which is added in the form of data, edit data, and delete data through the admin page. Thewebsite is expected to be a system that can be useful for all parties